Problems of Allocation of Production Factors in Enterprises Working the Soil: Application of Cobb-Douglas Production Function - KOTULIC, Rastislav; PAVELKOVA, Jana; VOZAROVA, Ivana Kravcakova; VAVREK, Roman (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018DO - 10.14505//jemt.v9.5(29).03, 2018)
Agriculture is an important industry that is often pursued by government and that is often the subject of many international disputes. Given the importance of this sector it is necessary to measure its performance. The aim of this paper is to evaluate the effectiveness of production inputs in the selected entities working on the land using the production analysis. The presented and very specialized issue fills a gap in the field of research for the period around the turn of the second millennium. This period was specific mainly for transformation and integration processes related with the accession of the Slovak Republic to the European Union. We assume that the transformation process of the Slovak economy from a centrally planned to a market economy was not finished during the monitoring period and left its marks in the form of inefficient allocation of productive resources in the agricultural production.